Desempeño funcional y características demográficas de pacientes con discapacidad asociados a parálisis cerebral infantil en menores de 14 años en los servicios de rehabilitación del Hospital II-2 Tarapoto y Hospital II Essalud – Tarapoto, periodo julio – noviembre de 2015 - Ynoue Mendoza, Mario Sergio (2016)
Objective: To know the functional performance and demographic characteristics of patients with disabilities associated with Cerebral Palsy in children less than 14 years of age in the rehabilitation services of II-2 Tarapoto Hospital and II EsSalud - Tarapoto Hospital, from July to November 2015. Methodology: It’s a descriptive, transversal study; the sample consisted on 14 patients who compiled the inclusion criteria; the clinical history and the WeeFIM scale as an interview during the consultation was used. Results: Regarding functional performance, the degree of complete dependence predominated in the areas of personal care and mobility, with 59.8% and 57.1%, respectively; In the cognitive area there was equivalence in degrees of complete and modified dependence, with 35.7% for each. The highest levels of disability (50- 95% of disability) and total (96-100% of disability) were presented, with 35.7% for each case. Among the demographic characteristics, 42.9% of patients are in the school stage (6-14 years); 50% are male and 50% female; 85.7% come from the urban area; 100% receive financial help from only the family; 85.7% have regular care; In the chronological order of birth, 57.1% corresponded to the first child. In terms of risk factors, patients had a gestational age <37 weeks in 64.3% of the cases, and 35.7% had a history of having recurrent UTI during gestation. Conclusions: The degree of complete dependency in the areas of personal care and mobility prevailed; The greater number of patients show degrees of severe and total disability. There was no predominance in sex, gestational age <37 weeks, and the history of recurrent urinary infection during pregnancy were the risk factors present in most patients